Structural, optical, and magnetic properties of Ag+, Mn+ and Ar+ ions implanted ZnO thin films: effect of implantation dose and stopping energy - Lim, Weon Cheol; Singh, Jitendra Pal; Song, Jonghan; Seong, Tae-Yeon; Chae, Keun Hwa (Royal Society of Chemistry, 2022)
Herein, we systematically studied the effect of various excitation processes on the structural, optical, and magnetic properties of ZnO films implanted with 80 keV Ar+, 110 keV Mn+, and 190 keV Ag+ ions. Four different doses of 1 x 10(13), 1 x 10(14), 1 x 10(15), and 2 x 10(16) ions per cm(2) were used for implantation. It was observed that the structural, optical, and magnetic properties of the implanted samples were dominantly affected at the highest dose of 2 x 10(16) ions per cm(2). For lower doses, insignificant changes in these properties were observed. A comparison of various processes involved in the implantation process shows that both the electronic excitation and nuclear excitation processes are responsible for the changes in the structural, optical, and magnetic properties of the implanted ZnO films.